Clinical utility of serodiagnostic testing in pediatric inflammatory bowel disease - Urlep Žužej, Darja (Zdravniški vestnik, 2006)
Background. Among children and adolescents, the diagnosis of inflammatory bowel disease (IBD) is often missed or delayed because of the nonspecific nature of the clinical symptoms. In such instances noninvasive and accurate diagnostic tests that would accurately distinguish IBD from functional disorders would be most valuable to clinicians. Several serological markers have been used as non-invasive diagnostic tools in IBD pediatric patients. The aim of our study was to determine the prevalence and diagnostic accuracy of perinuclear antineutrophil cytoplasmic antibodies (p-ANCA), anti-Saccharomyces cerevisiae antibodies (ASCA), anti-exocrine pancreatic antibodies (PAB) and anti-goblet cells antibodies (GAB) alone and in combination in children and adolescents with IBD. Patients and methods. Serum specimens were analyzed for p-ANCA, ASCA IgG, ASCA IgA, PAB and GAB antibodies in 49 children and adolescents with confirmed IBD and 53 non-IBD controls. P-ANCA, PAB and GAB antibodies were determined by indirect immunofluorescent test and ASCA by enzyme-linked immunosorbent assay. All patients with Crohn's disease (CD) had genotyping performed using a sequence specific PCR directed against the wild type and the three principal mutations of NOD2/CARD15 gene. Disease location, body mass index (BMI) and disease activity by pediatric Crohn's disease activity index (PCDAI) at the time of diagnosis were determined in CD patients. Results. The prevalence of p-ANCA in patients with UC and ASCA in CD patients was high (82.3 % and 67.9 %, respectively). Positivity for PAB antibodies in CD and GAB in UC was lower (35.7 % and 23.5 %, respectively). Accuracy data (sensitivity, specificity, PPV, NPV, respectively) for differentiating IBD from non-IBD controls were as follows: p-ANCA: 82 %, 100 %, 100 %, 94 %; ASCA IgG: 68 %, 94 %, 86 %, 84 %; ASCA IgA: 54 %, 100 %, 100 %, 80 %; PAB: 36 %, 98 %, 91 %, 74 %; GAB: 23 %, 100 %, 100 %, 80 %. In distinguishing CD from UC we found out the following accuracy data (sensitivity, specificity, PPV, NPV, respectively): p-ANCA: 82 %, 82 %, 74 %, 88 %; ASCA IgG: 68 %, 100 %, 100 %, 65 %; ASCA IgA: 54 %, 100 %, 100 %, 57 %; PAB: 36 %, 100 %, 100 %, 49 %; GAB: 23 %, 100 %, 100 %, 68 %. There were no significant association between ASCA positivity and the three major mutations of NOD2/CARD15 gene, disesase location and family history in CD patients, however an association between BMI and disease activity at the time of diagnosis was found out. Conclusions. Specificity and positive predictive value of serological markers p-ANCA, ASCA IgG, ASCA IgA, PAB and GAB for IBD alone and in combination are high and which make them useful in diagnosis of inflammatory bowel disease in day-to-day clinical practice, particulary in making decision about performing invasive diagnostic procedures. Because of low sensitivity they are less useful as screening tests for inflammatory bowel disease in pediatric population.
Keywords: Adolescent; Child; Colitis, Ulcerative; Crohn Disease; Crohnova bolezen; črevesne bolezni; diagnostika; genetics; Genetika; Inflammatory Bowel Diseases; Mladostnik; otroci; Otrok; Serologija; Serology; serološka diagnostika; Ulcerativni kolitis; Vnetne črevesne bolezni